Anti-Corruption Advocacy in Building Inclusive and Accountable Institutions (SDG 16): A Global Bibliometric Analysis - Yuliansyah, Romi Ali; Rachman, Balqis Azkia (Universitas Negeri Gorontalo, 2025)
Corruption continues to pose a major challenge in achieving inclusiveand accountable governance as outlined in Sustainable Development Goal (SDG)16. Although numerous anti-corruption initiatives have been implementedglobally, systematic and comprehensive analyses of academic research onadvocacy efforts to strengthen transparent and responsible institutions remainlimited. This study aims to examine global publication trends, patterns ofscholarly collaboration, and thematic developments in anti-corruption advocacyresearch. Employing a quantitative descriptive approach through bibliometricanalysis, data were collected from the Scopus database for the 2020–2025period. The metadata were processed and visualized using VOSviewer softwareto identify publication patterns, key authors, contributing countries, institutions,and keyword relationships. The results reveal a significant rise in globalpublications on anti-corruption advocacy, dominated by contributions fromChina, the United States, and the United Kingdom. Institutional analysis indicatesthat universities with strong research capacity—particularly in East Asia—play acentral role in advancing this field, while developing nations remainunderrepresented. Thematic mapping identifies three main areas of focus:institutional transparency and accountability, civil society advocacy andparticipation, and digital governance and integrity. These findings suggest aparadigmatic transition from punitive legal approaches toward preventive,participatory, and technology-based strategies in addressing corruption. Thestudy emphasizes that strengthening anti-corruption advocacy requires globalacademic collaboration, inclusive research partnerships, and the application ofinnovative, data-driven governance models to effectively advance the objectivesof SDG 16.